Infrastruktura techniczna a konkurencyjność regionów - Biegun, Krzysztof (Technical Infrastructure versus Competitiveness of the Regions, 2007)
Degree of technical infrastructure development is one of the main determinants of economic growth and development. Low degree of technical infrastructure development may decrease international competitiveness of Polish regions on the Common Market and become a strong barrier of economic development. Integration into the EU will be very important for speed and directions of infrastructure development process in Poland, among other things through liberalization of markets, development of Trans European Networks and, last but not least, financial support.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 270-290